80 UPM students volunteer for Northeast Monsoon Flood Relief Mission 2022 - Juferi, Noor Eszereen (Pusat Strategi dan Perhubungan Korporat, Universiti Putra Malaysia, 2022)
SERDANG, Dec 31 - A total of 80 students from Universiti Putra Malaysia (UPM) have volunteered for the Northeast Monsoon Flood Relief Mission 2022 to assist flood victims at Tumpat, Kelantan and Besut, Terengganu.